2022
DOI: 10.1038/s41524-022-00710-0
|View full text |Cite|
|
Sign up to set email alerts
|

The elphbolt ab initio solver for the coupled electron-phonon Boltzmann transport equations

Abstract: is a modern Fortran (2018 standard) code for efficiently solving the coupled electron–phonon Boltzmann transport equations from first principles. Using results from density functional and density functional perturbation theory as inputs, it can calculate the effect of the non-equilibrium phonons on the electronic transport (phonon drag) and non-equilibrium electrons on the phononic transport (electron drag) in a fully self-consistent manner and obeying the constraints mandated by thermodynamics. It can calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Analytical theories of these scattering phenomena for a plain parabolic band date back many decades, but developed only recently are the computational tools suitable for treating DFT band structures within nonprohibitive computing time, at least for simple structures. Many of these methods rely on density-functional perturbation theory (DFPT), , some additionally on interpolation via Wannier functions, to obtain electron–phonon scattering matrix elements, which are highly cumbersome for large, complex, low-symmetry systems such as S 1– x Se x at even a relatively coarse k -point mesh.…”
Section: Methodsmentioning
confidence: 99%
“…Analytical theories of these scattering phenomena for a plain parabolic band date back many decades, but developed only recently are the computational tools suitable for treating DFT band structures within nonprohibitive computing time, at least for simple structures. Many of these methods rely on density-functional perturbation theory (DFPT), , some additionally on interpolation via Wannier functions, to obtain electron–phonon scattering matrix elements, which are highly cumbersome for large, complex, low-symmetry systems such as S 1– x Se x at even a relatively coarse k -point mesh.…”
Section: Methodsmentioning
confidence: 99%
“…While metallic systems suffer mostly from too coarse momentum grids, gapped systems tend to exhibit massive numerical instabilities. 17 Due to the additional Γ-smearing in our formalism, this problem is absent for reasonably large scattering rates (Γ ≥ 10 −6 eV) and reasonable band gaps (∆ < 10eV) at all temperatures when using Eq. ( 70).…”
Section: Chemical Potential Searchmentioning
confidence: 96%
“…Being agnostic to the input's origin, LinReTraCe can be used in a variety of settings, including electronic structures from tight-binding or Wannier projections [5], density functional theory (DFT) [6], many-body perturbation theory [7,8], dynamical mean-field theory (DMFT) [9,10], or approaches beyond [11,12]. Scattering amplitudes and many-body renormalizations can be phenomenological, extracted from electronic self-energies (obtained, e.g., from DMFT), or could incorporate results from electron-phonon codes [13][14][15][16][17][18][19]. In this release we include interfaces to the DFT codes WIEN2k [20,21] and VASP [22], the band interpolation tool of BoltzTraP2 [23,24], maximally localized Wannier functions of Wannier90 [25], as well as tools for general tight-binding systems.…”
mentioning
confidence: 99%
“…We also point out that electrons are taken to be in equilibrium when calculating ph-el scattering rates, which thus leads to the decoupled BTE. More rigorously, those interactions between non-equilibrium electrons and phonons should also be considered within the coupled el-ph BTEs [30]. Recent studies have found that it has significant effects on Seebeck coefficient and mobility in doped semiconductors [31].…”
Section: Phonon-electron Scatteringmentioning
confidence: 99%